Improvements to institutional mechanism of formation and development of human resources on the regional level (Journal of Economic Research & Business Administration, 2015)
Currently, the foundation of industrial-innovative development of the economy of the region should be based on active economic, social and personnel policy, focused on the achievement of socio-economic progress and providing ways to achieve their goals. The article considers the possibility of the integrated management of the formation and development of human resources at the regionallevel. Management of formation and development of human resources in the region involves different areas and forms of human exposure as a carrier of labor, political, and social function. Also considered the principles and algorithm development system of human resources development. Focuses on the current urgent need to increase mutual social responsibility and activity of small, medium and large businesses, educational institutions, government agencies, non-governmental organizations in the creation of conditions for the development of human resources and employment potential of the area. The involvement of all of the parties in the development, financing and implementation of regional programs of human resources will be a powerful factor in resolving the identified problem.